2019
DOI: 10.1038/s41598-019-46283-9
|View full text |Cite|
|
Sign up to set email alerts
|

A multicentric evaluation of dipstick test for serodiagnosis of visceral leishmaniasis in India, Nepal, Sri Lanka, Brazil, Ethiopia and Spain

Abstract: Visceral leishmaniasis (VL) is one of the leading infectious diseases affecting developing countries. Colloidal gold-based diagnostic tests are rapid tools to detect blood/serum antibodies for VL diagnosis. Lack of uniformity in the performance of these tests in different endemic regions is a hurdle in early disease diagnosis. This study is designed to validate a serum-based dipstick test in eight centres of six countries, India, Nepal, Sri Lanka, Brazil, Ethiopia and Spain with archived and fresh sera from 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…As an alternative, a dipstick test containing L. ( L. ) donovani membrane antigens was developed, presenting sensitivity and specificity of 100% in Indian and Brazilian patients with VL ( Table 1 ) [ 94 ]. This test was evaluated later for VL, using sera from more than 1000 subjects from eight centers in six endemic countries (India, Nepal, Sri Lanka, Brazil, Ethiopia, and Spain) [ 93 ]. The overall sensitivity and specificity for all these regions were 97.1% and 93.44%, respectively, and a better performance of this test was found compared to the rK39 rapid test (see below) in these regions [ 93 ].…”
Section: Immunological Methods For Diagnosis Of Leishmaniasismentioning
confidence: 99%
“…As an alternative, a dipstick test containing L. ( L. ) donovani membrane antigens was developed, presenting sensitivity and specificity of 100% in Indian and Brazilian patients with VL ( Table 1 ) [ 94 ]. This test was evaluated later for VL, using sera from more than 1000 subjects from eight centers in six endemic countries (India, Nepal, Sri Lanka, Brazil, Ethiopia, and Spain) [ 93 ]. The overall sensitivity and specificity for all these regions were 97.1% and 93.44%, respectively, and a better performance of this test was found compared to the rK39 rapid test (see below) in these regions [ 93 ].…”
Section: Immunological Methods For Diagnosis Of Leishmaniasismentioning
confidence: 99%
“…Recombinant leishmanial antigens such as rKLO8, rKE16 and rK28 are few of them [6,7,8,9]. We in our previous studies have reported the diagnostic value of antigens, LAg, through various immunological techniques like ELISA, immunoblot, and dipstick test [5,10,11].…”
Section: Development Of Rk39mentioning
confidence: 99%
“…Recombinant leishmanial antigens such as rKLO8, rKE16 and rK28 are few of them [6][7][8][9]. In our previous studies, we have reported the diagnostic value of Leishmania promastigote membrane antigens (LAg) through various immunological techniques such as ELISA, immunoblot and dipstick test [5,10,11]. Moreover, anti-leishmanial antibodies in the sera of active and cured VL patients have shown variable reactivity against several proteins of LAg in the immunoblot assay [12].…”
Section: Introductionmentioning
confidence: 99%